2018
DOI: 10.1186/s40510-018-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the treatment of unilateral posterior cross-bite: a three-dimensional finite element stress analysis study

Abstract: BackgroundStress relieving corticoto mies during the treatment of maxillary expansion are needed in adult patients.MethodsThree-dimensional (3D) finite element model was prepared, and finite element analysis was processed to evaluate the stress distributions within the skull and maxillary teeth during surgically assisted rapid maxillary expansion (SARME) treatment.ResultsExpansion forces generated more stress on the corticotomy-applied part of the maxilla. The stress levels decreased dramatically above the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
1
0
2
Order By: Relevance
“…Chung et al [34] have stated that corticotomy cuts can reduce the resistance of alveolar bone to orthodontic tooth movement by breaking the bone integrity. In line, a recent study showed that the stress dramatically declined during maxillary expansion above the corticotomy line, and they stated that the maxillary half splitted by the corticotomy cut could be expanded more easily when compared to the part with no corticotomy [24]. Our results also demonstrated that transmission of the stress at the palatal alveolar process of the anchor teeth was interrupted in the third scenario by the horizontal corticotomy line.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Chung et al [34] have stated that corticotomy cuts can reduce the resistance of alveolar bone to orthodontic tooth movement by breaking the bone integrity. In line, a recent study showed that the stress dramatically declined during maxillary expansion above the corticotomy line, and they stated that the maxillary half splitted by the corticotomy cut could be expanded more easily when compared to the part with no corticotomy [24]. Our results also demonstrated that transmission of the stress at the palatal alveolar process of the anchor teeth was interrupted in the third scenario by the horizontal corticotomy line.…”
Section: Discussionsupporting
confidence: 85%
“…This study was performed with the approval of Gazi University Institute of Health Sciences (22/12/2014-E.131593). The computed tomography (CT) images of a previously conducted adult maxillary bone with a skeletal class 1 adult patient without any craniofacial anomalies [24] were acquired at 0.2 mm intervals in the axial direction perpendicular to the occlusal plane. Three-dimensional (3D) model of the skull and the maxillary bone was constructed by 3D Doctor software.…”
Section: Methodsmentioning
confidence: 99%
“…Ortodonti literatüründe, sonlu elemanlar stres analizi yöntemiyle elde edilen üç boyutlu araştırma modellerinin oldukça sık kullanıldığı belirlenmiştir. [27][28][29][30][31][32] Aynı zamanda ortodontik ve ortopedik kuvvetlerin dentofasiyal kompleksi oluşturan anatomik yapılar üzerindeki biyomekanik etkileri de bu modeller üzerinde değerlendirilmiştir. [27][28][29]32 Yapılan çalışmalar sonucunda, sonlu elemanlar stres analizi yönteminin ortodonti mekaniklerinin seçiminde kullanılabileceği rapor edilmiştir.…”
unclassified
“…[27][28][29][30][31][32] Aynı zamanda ortodontik ve ortopedik kuvvetlerin dentofasiyal kompleksi oluşturan anatomik yapılar üzerindeki biyomekanik etkileri de bu modeller üzerinde değerlendirilmiştir. [27][28][29]32 Yapılan çalışmalar sonucunda, sonlu elemanlar stres analizi yönteminin ortodonti mekaniklerinin seçiminde kullanılabileceği rapor edilmiştir. 27,29,30,32 Model I ve Model II'e ait dişlerde saptanmış olan en yüksek stres miktarını mandibular kondil ve ramus bölgesi izlemektedir.…”
unclassified